Vigorous physical activity and self-rated health during adolescence: A cross-sectional survey - Wang, Yongkang; She, Weizhong; Chi, Guijun; Wang, Junsheng (Frontiers in Public Health, 2022)
Background Despite the positive relationship between self-rated health and general physical activity, very little research has touched upon the relationship between self-rated health and vigorous physical activity. Such research will help to promote self-rated health among adolescents by addressing the close relationship between self-rated health and the components of physical activity. Purpose In this study, the relationship between self-rated health and vigorous physical activity among Chinese adolescents were analyzed. Methods The current study was based on a collaborative survey conducted by the WHO in several nations, and the data generated by Health Behavior in School-aged Children every 4 years on health behavior were adopted. The school class was taken as a basic unit for sampling. Cluster sampling was performed systematically, and the possibility was proportional to the population. The sampling was conducted to collect typical cases. The class teachers were informed of the sampling activities, and they were to collect data on the students by distributing the questionnaires. Results The research included 116,828 respondents from 36 countries. Among them, 51.82% were girls and 48.18% were boys. A total of 98.54% of the respondents considered their health status as fair or above when completing the questionnaire, while 1.46% believed that their health status was poor. Moreover, more than 86% of the respondents participated in vigorous exercise more than weekly, and better self-health ratings were found among respondents who exercised more than weekly (once a week: OR = 1.95, CI: 1.86–2.04; two or three times a week: OR = 1.69, CIL: 1.63–1.76; four or six times a week: OR = 1.30, CI: 1.25–1.35). Certain respondents reported better results for self-rated health (4–6 h every week: OR = 1.36, CI: 1.30–1.43; 2 or 3 h every week: OR = 1.48, CI: 1.42–1.55; 1 h every week: OR = 1.64, CI: 1.57–1.72). Conclusion In this study, empirical evidence is provided for the relationship between self-rated health and vigorous physical activity among adolescents. From the results, it can be observed that there is a positive relationship between self-rated health and vigorous physical activity among adolescents.